- Edexcel, Module - C2, Chapter- Sequences and Series
- AQA, Module - C2, Chapter - Sequences and Series
- OCR, Module - C2, Chapter - Sequences and Series
The Binomial Expansion, is a theorem which allows us to expand (a + b)^n, where n is an integer. (a and b are just what i've used it, they can be any letters).
Why we need it ?
Let's say we have to expand the following terms :
(x + y)^1 = x + y
(x + y)^2 = x^2 + 2xy + y^2
(x + y)^3 = (x + y)(x + y)^2
= (x + y)(x^2 + 2xy + y^2)
= x^3 + 3x^2y + 3xy^2 + y^3
As we see, when increasing the power, (n) we get more and more terms, and it becomes more and more confusing, say we had to expand (x + y)^7, this would mean we would get 8 terms, after expanding the bracket 7 times, and then simplifying it. This would be a tedious and extremely long !
The Binomial theorem therefore allows us to expand the binomials ( two terms e.g. x + y or x + 3y or a - 3b). In each term of the expansion, there will be a coefficient of the term, these coefficients are either determined by Pascal's Triangle or Factorial Formula.
Let's see how this works, with the examples above... Let's expand (x + y)^3 using the theorem :
Binomial Theorem = To expand the binomial (x + y)^n, it can be written in the form :
|This is the binomial coefficient, where n is the power and k is the increasing value till we reach n.|
Let's use take our example using the theorem :
(x + y)^2 = (2,0) x^2 y^0 + (2,1) x^1 y^1 + (2,2) x^0 y^2
*The brackets are the binomial coefficients in blue , which are calculated using the formula :
* We finish the binomial expansion when the binomial coefficient is (n,n) in this case (2,2), and when the x term has reached to the power 0 (which is 1), and the y term is to power n (in this case 2) . (Remember anything to the power 0 = 1 and anything to the power 1 = itself )
Let's simplify it down further, these are the binomial coefficients for each term :
! = Factorial (it calculates the product of all the positive integers less than or equal to some integer n)
(e.g. 4! = 4 x 3 x 2 x 1 = 24)
Note : 1! = 1 and 0! = 1
(2,0) = 2! / [ 0! (2 -0)! ]
= 2 / [ 1 x 2 ]
= 2 / 2
(2,1) = 2! / [ 1! (2 -1)! ]
= 2 / [ 1 x 1 ]
= 2 /1
(2,2) = 2! / [ 2! (2 -2)! ]
= 2 / [ 2 x 1]
= 2 / 2
So we have calculated the binomial coefficients for the terms, giving us :
(x + y)^2 = x^2 + 2xy + y^2
Pascal's Triangle ( Second way to find binomial coefficients - helps when n is small)
Another way to find the binomial cofficients, is the Pascal's Triangle. We start with n = 0, and start with number 1. Each row, will list the binomial cofficients in order of the expansion, each starting with 1 and ending with 1, depending on n.
To find the coefficient underneath, two gaps, we simply add the coefficients above it.
n = 0 1
n = 1 1 1
n = 2 1 2 1
n = 3 1 3 3 1
n = 4 1 4 6 4 1
n = 5 1 5 10 10 5 1
* The Triangle goes on as n increases, and the number of coefficients is always ( n + 1)
* The Triangle is symmetrical halfway, so we see that the first half of the coefficients of terms, is always the same as the second half
* Each row of the triangle starts and ends with 1 (meaning the first coefficient and last coefficient of any expansion is always 1)
Double check the expansion (x + y)^2 , where n = 2,
Check the row n = 2
The binomial coefficients should be 1, 2 and 1
1x^2 + 2xy + 1y^2
So we've seen how to expand expressions in the form (x + y)^n, and use two methods of working out the binomial coefficients. In the next post I will show you a couple of examples, and another expansion theorem, which allows us to expand algeabraic expressions in the form (1 + x)^ n.